Job satisfaction of rural medical interns: A qualitative study. (26th May 2020) - Isaacs, Anton N.; Raymond, Anita; Jacob, Angela; Hawkings, Philippa
Abstract: Objective: To study reasons for job satisfaction and dissatisfaction among interns. Design: Using a qualitative methodology, one‐to‐one interviews were conducted with interns. Setting: The study was based at a Victorian Rural Intern Training program. Participants: Twelve interns from the program were interviewed during their final rotation. Main outcome measures: Reasons for job satisfaction and dissatisfaction among rural interns. Results: Reasons for job satisfaction included feeling supported in the workplace as well as getting quality supervision, teaching and clinical exposure. Reasons for job dissatisfaction included poor access to administration, unduly stressful working situations, lack of support for mental health and well‐being, and poorly organised teaching sessions. Conclusion: The internship experience, together with the people they are influenced by, can determine a doctor's future career pathway. It is therefore vital for internship coordinators and hospital managers to facilitate a positive internship experience. The findings have implications for human resource management policy and practice in rural hospitals.